High Prevalence of Potentially Inappropriate Medications among Geriatric Cardiovascular Patients: A Cross-Sectional Study at a Hospital in Eastern Indonesia - Nelly Kurniawati; Masni D; Sri Rahayu; Oktaviano Mariano Alberthino Sola (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Potentially Inappropriate Medications (PIMs) are a frequent concern among elderly patients with cardiovascular disease (CVD), where polypharmacy and age-related vulnerability increase the risk of adverse outcomes. This study investigated the prevalence and contributing factors of PIMs in elderly CVD patients at dr. TC Hillers Hospital, Maumere, Indonesia. Both the 2023 American Geriatrics Society (AGS) Beers Criteria and the Screening Tool of Older Persons’ Prescriptions (STOPP) version 3 were applied to assess PIMs . A hospital based cross sectional design was implemented from August to September 2023, enrolling outpatients aged 65 years and above with confirmed CVD diagnose. Data regarding sociodemographic characteristics, comorbidities, and medications were collected from medical records. Among 110 patients, 141 PIM events (18.1%) were identified from 779 medications using Beers 2023, and 168 PIM events (21.6%) using STOPP v3. Chi-square test was used to examine differences in the prevalence of PIMs across demographic and clinical characteristics. The overall patient level prevalence of PIMs was 71% based on Beers 2023 and 68% based on STOPP v3. Polypharmacy was the strongest determinant, even in the absence of comorbidities. A higher Age-Adjusted Charlson Comorbidity Index (ACCI) scores showed no significant association with PIMs when using Beers 2023, but was significantly with STOPP v3. No significant associations were found with age or gender. Proton pump inhibitors, diuretics, and the combination of spironolactone with RAS inhibitors were the most frequent PIMs. In conclusion, PIM prevalence among elderly CVD outpatients in Maumere is alarmingly high, reflecting the complexity of cardiovascular pharmacotherapy.